Isaac Abarbanel's Defense of the Authority, Reliability and Coherence of Biblical Historiography - Has, Yaʾir (Hebrew Union College annual, 2011)
The combined influence of Abarbanel's cultural and religious environment and religio-philosophical views made him aware of the existence of some perplexing questions regarding the Former Prophets (FP) which seemed to run counter to the axiom of Scripture's divine infallibility. In fifteenth-century Iberia, royal historiography was looked upon with relative suspicion and was regarded as biased and unreliable. The integrity of the narratives of the Old Testament had been under attack from Christian polemicists for centuries. Leading Christian theologian Alphonso Tostado had raised the question of the prophetic essence and authority of books that related to the past instead of the future. And Abarbanel's own prophetology did not allow for non-mosaic prophetic works written in a clear and lucid prose style. In order to meet this manifold challenge, Abarbanel developed a detailed theory concerning the formation of the Bible's historical books, at the core of which stands a definition of prophecy as any piece of knowledge unknowable unless through divine revelation. According to this theory the prophetic authors of the FP relied on earlier historical documents, but only by means of divine inspiration were they able to sift truth from falsehood and the necessary from the extraneous. This theory, though, apologetic as it is, cannot be completely reconciled with historiographical views expressed by Abarbanel in other contexts.